MENDORONG DAYA SAING INDUSTRI DI MADURA MELALUI PENDEKATAN KLASTER INDUSTRI - Abdul Azis Jakfar (AGROINTEK, 2014)
The development of industrial clusters is considered the most effective solution in the development of the local economy of a region. Industry cluster development means developing industry that is likely to have high competitiveness in domestic and global markets. The impact area has its own competitiveness against other regions. Developing industry in Madura necessary preparations. In addition to the selection of industrial areas suitable for Madura, there are four pillar industries (raw materials, human resources, technology, and capital) that need treatment in order to achieve the direction and purpose of building industry in Madura. Based on available resources Madura the agro-industry is the entrance and the main driver of industrialization Madura. Four districts should be able to integrate the strategic plan development and construction agropolitan integrated agribusiness system, then directed to build Madura industry based on: maritime, tourism and the creative economy. Cluster approach is not just a grouping of industries, but it also should include linking between the core industry with related industries, industry suppliers, supporting industries, and buyers, all of which are supported by the supporting institutions. Madura economy is expected to increase through the cluster approach in its potential industries. Four districts in Madura should focus on the prospective industries to improve product competitiveness. Increasing the competitiveness of industry in Madura can be carried out by(1) Improving the skills of human resources, (2) Improved production technology, (3) Development of product design and packaging design, (4) Promotion and improving market access.